Sensitive and Simultaneous Determination of Hydroquinone and Catechol in Water Using an Anodized Glassy Carbon Electrode with Polymerized 2-(Phenylazo) Chromotropic Acid - Miao Zhang; Chuang-ye Ge; Ya-feng Jin; Liang-bin Hu; Hai-zhen Mo; Xiao-bo Li; Hao Zhang (Journal of Chemistry)
Hydroquinone (HQ) and catechol (CT) are considered as environmental pollutants with high toxicity. We have developed a simple electrochemical sensor using an anodized glassy carbon electrode modified with a stable 2-(phenylazo) chromotropic acid- (CH-) conducting polymer (PCH/AGCE). The PCH/AGCE sensor showed good electrocatalytic activity and reversibility towards the redox of HQ and CT in phosphate buffer solution (PBS, pH 7.0). The cyclic voltammetry (CV) in mixed solution of HQ and CT showed that the oxidation peaks of them became well resolved with a peak separation of 0.1 V. The detection limits of HQ and CT were 0.044 and 0.066 μM, respectively, in a wide linear response range of 1–300 μM for both. Moreover, the sensor displayed an excellent selectivity in the presence of common interferences. This study provided a simple, sensitive, and high recovery method for simultaneous and quantitative determination of HQ and CT in aqueous medium.